PENGARUH KEPEMIMPINAN KEPALA MADRASAH TERHADAP KINERJA GURU PADA MAS SEKABUPATEN TANAH DATAR - Ikhwandra Ikhwandra (IAIN Batusangkar, 2016)
Effect of Leadership Head Madrasah on The Performance Teacher In MAS se-Kabupaten Tanah Datar. The purpose of this research was to reveal how extend the correlations of of the school principal’s leadership and the teamwork towarthe teachers’ performance of Privat Islamic Senior High at Tanah Datar Regency.There were three hypotheses to be tested : the school principal’s leadership contributed significantly toward the teachers’ performance; of Privat Islamic Senior High at Tanah Datar Regency.Research population were all teacher of privat Islamic Senior High at Tanah Datar Regency of 386 teachers from which 59 teachers were selected as a research sample by means of the stratified proportional random sampling technique. The result of data analyses show that a) the school principal’s leadership contributed significantly (24,1%) toward the teachers’ performance;Kata kunci: Kepemimpinan, kepala madrasah, kinerja guru